Can nocturnal emergency surgery be reduced?. Issue 6438 (21st July 1984) - Sherlock, D J; Randle, J; Playforth, M; Cox, R; Holl-Allen, R T
Abstract : A prospective study of emergency operations was performed over three months in a district general hospital. Before starting surgery surgeons completed a questionnaire recording clinical details together with time of admission and were asked to state whether in their opinion the case could be safely deferred until the next morning assuming operating time was available. Of 251 operations performed, forms were completed for 244. According to the surgeons, 62 could have been safely deferred, and subsequent independent analysis indicated a further 24 could also have been safely postponed, giving a total of 86 cases (35%). Of the remainder, 71 were started between 2300 and 0900, and of these 51 (71%) were major operations requiring an experienced surgeon. The results suggest that, although the volume of nocturnal major surgery could not be reduced, the introduction of a daily emergency theatre session for cases seen during the day and those which could be deferred from the previous night would appreciably reduce the overall workload of nocturnal surgery at present done by the resident junior staff. This study will have important implications if, as has been suggested, the number of junior medical staff on call at night for emergencies is reduced.